PERATAAN LABA DAN VARIABEL-VARIABEL YANG MEMPENGARUHINYA (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ) - Purweni Widhianningrum (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
This study aimed to determine the effect of managerial ownership, institutional ownership, debt financing, ownership dispersion, profitability, and firm size simultaneously and partially on income smoothing.This study uses manufacturing companies listed on the Jakarta Stock Exchange as an object of research. Based on purposive sampling method there are 147 companies that found the above criteria. Data analysis method used is multiple regression analysis. The results of this study showed that ownership dispersion and size of company that has a significant effect partially on income smoothing. The larger company and expanding company's ownership structure has greater freedom to report better earnings.